KONDISI SOSIAL-POLITIK DINASTI BANI ABBASIYAH DAN PENGARUHNYA TERHADAP PENDIDIKAN ISLAM - Muhammad Amiruddin Dardiri; Waluyo Waluyo; Anzar Aquil (STAI Asy-Syukriyyah, 2023)
The Abbasid dynasty had given a very high contribution to Islamic civilization in the history of Islam which was marked by the development of Islamic educational institutions and science. This development cannot be separated from the socio-political conditions that occurred at that time. Some of the factors that determine the development of Islamic education and science are the geographical conditions of the Abbasid dynasty located in Baghdad, far from Mecca and Medina which led to the emergence of ijtihad-ijtihad by ulama’ Ahl-Ra'yi; pluralism of people characterized by the presence of non-Arab or militant groups who are very militant; and the ideological feud of kalam, fiqh, and Sufism. In this case, there is a power relationship between government and science. The role of government is very important in determining the direction and form of Islamic education. A very rational style of religious understanding helped shape the development of Islamic education and science. This can be seen from the adoption of the mu'tazilah ideology as the official state ideology in Islamic theology, and the predominance of the ulama 'ahl-Ra'yi in fiqh.